2020
DOI: 10.1111/ceo.13754
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cataract surgery on depression and cognitive function: Systematic review and meta‐analysis

Abstract: Importance In elderly people, visual impairment is associated with depressive symptoms and cognitive decline. However, the impact of cataract surgery on depression and cognitive impairment is still controversial. Background To evaluate the effect of cataract surgery on depression and cognitive status in the elderly. Design This study was a meta‐analysis. Participants Patients with age‐related cataract who underwent cataract surgery were recruited for this study. Methods A literature search was performed on Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…7 Vision impairment as a modifiable risk factor warrants careful scrutiny given that rehabilitation of vision impairment such as cataract surgery and visual training may help to prevent or delay cognitive decline in older adults. 82,83 Therefore, screening and treating for vision impairment in older adults, especially in low-and middle-income countries, may mitigate the global burden of dementia significantly.…”
Section: Discussionmentioning
confidence: 99%
“…7 Vision impairment as a modifiable risk factor warrants careful scrutiny given that rehabilitation of vision impairment such as cataract surgery and visual training may help to prevent or delay cognitive decline in older adults. 82,83 Therefore, screening and treating for vision impairment in older adults, especially in low-and middle-income countries, may mitigate the global burden of dementia significantly.…”
Section: Discussionmentioning
confidence: 99%
“…90,91 Another meta-analysis found a significant reduction in depression after cataract surgery. 92 A review done by members of this Commission, in addition to the rapid review, found an association between vision impairment and dementia, and suggested that interventions to improve vision could possibly slow down cognitive decline (panel 1).…”
Section: Vision Impairment and Other Health Conditionsmentioning
confidence: 99%
“…Cataract surgery represents one of the most commonly performed procedures in the world ( Pascolini and Mariotti, 2012 ). Advancements in anesthesia and surgical techniques made it possible to perform most of the procedures for cataract extraction under topical anesthesia ( Pellegrini et al, 2020 ; Lundström et al, 2021 ). On the one hand, this achievement has greatly reduced operating times and side effects related with local or general anesthesia ( Giannaccare et al, 2021 ; Lundström et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%